Analisis Dampak Terjadinya Perceraian (Pembagian Harta & Hak Asuh Anak) : Studi Di Pengadilan Negeri Medan - Rona Rindamelani Hutasoit; Cindy Ayu Lestari; Hanna Izzati Ar Raudhah; Parlaungan Gabriel Siahaan; Dewi Pika Lbn Batu (Garuda: Jurnal Pendidikan Kewarganegaraan Dan Filsafat, 2023)
In this article, we will examine the impact of divorce (Division of Property & Child Custody) where this study was conducted at the Medan District Court. This divorce has a lot of impacts, especially on children. However, this article will focus on the division of assets and child custody as a cause and effect of divorce. This research uses descriptive qualitative and normative legal methods through analytical and observational approaches, with data collection techniques based on literature studies and interviews. Divorce is triggered by various reasons, including disharmonious relations between husband and wife in terms of fulfilling biological needs, issues of different principles of life, differences in income in improving welfare, infidelity. The decision to divorce results in the division of property and child custody, where custody falls to the mother because the child is under 12 years old. Referring to Article 105 KHI, which explains that child custody in divorce with children under 12 years old is given to the mother. Meanwhile, the distribution of assets is in accordance with applicable Islamic law.